On one generalized integral transform of the Bessel type - Virchenko, N. O.; Chetvertak, M. O. (Reports of the National Academy of Sciences of Ukraine, 2014)
A generalization of the Bessel function is introduced. Its integral representation and basic properties are given. A generalized integral transform of the Bessel type is constructed. The inversion formula of this integral transform is given.